Effect of Combination Shunt Passive Filter Harmonic and Detuned Reactor on the K-Factor Changes of Transformer - Gumilar, Langlang; Afandi, Arif Nur; Aripriharta, -; Habibi, Muhammad Afnan; Kusumawardana, Arya (International Journal on Advanced Science, Engineering and Information Technology, 2023)
This paper describes the impact of changes in harmonic distortion on the value of the transformer K-Factor. The transformer has a capacity of 1.5 MVA and a K-Factor value of 1 under normal conditions. Techniques were installed to reduce harmonic distortion, shunt passive filter, and detuned reactor. Several condition scenarios were created to compare changes in harmonic distortion's value to the K-factors value. Scenario 1, the transformer works in harmonic conditions. The K-factor value of the transformer becomes 3.947101, and the new capacity of the transformer that can serve the load becomes 1.27 MVA. Scenario 2, a passive shunt filter was installed in the transformer circuit. Shunt passive filter can reduce IHD-V and THD-V values on PCC but increase IHD-I and THD-I values on the load side. The k-factor value fell to 1.5775, and the new capacity of the transformer increased to 1.44 MVA. The novelty of this paper is in scenario 3, a combination of a passive shunt filter and a detuned reactor was installed in the transformer circuit. The detuned reactor can limit the harmonic current that enters the harmonic filter. As a result, all values, including IHD-V, THD-V, IHD-I, and THD-I fell below the maximum harmonic distortion limit. The k-factor value fell to 1.0361, and the new capacity of the transformer increased to 1.49 MVA. The existence of a detuned reactor has been able to increase the performance of the passive shunt filter. The impact of the detuned reactor for future research is that it can be used to protect important equipment in the electric power system.